The House at Ujazdowskie 16 : Jewish Families in Warsaw after the Holocaust - Auerbach, Karen (Book collections on Project MUSE., 2013)
In a turn-of-the-century, once-elegant building at 16 Ujazdowskie Avenue in the center of Warsaw, 10 Jewish families began reconstructing their lives after the Holocaust. While most surviving Polish Jews were making their homes in new countries, these families rebuilt on the rubble of the Polish capital and created new communities as they sought to distance themselves from the memory of a painful past. Based on interviews with family members, intensive research in archives, and the families' personal papers and correspondence, the author presents an engrossing story of loss and rebirth, political faith and disillusionment, and the persistence of Jewishness.